IMPLEMENTASI AJARAN TRI PARĀRTHA DALAM KEHIDUPAN UMAT HINDU DI DESA ADAT BULELENG - Putu Buda Darma Laksana Buda; Ni Putu Eni Mila Yanti (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Tri Parartha is a doctrine in Hinduism, and Hindus believe that following it can help them live rich and pleasant lives. There are three components of Tri Parrtha: Asih, Punia, and Bhakti. Hindus must put the Tri Parrtha's teachings into practice in order to live peaceful lives. Living in harmony with one another is an example of a communal action that leads to happiness. The goal of this study is to inform the local community about the significance of the Tri Parrtha Teachings in the lives of Hindus in the Buleleng Traditional Village. Researchers employed a qualitative descriptive analytic approach to gather data for this study using techniques including observation, interviews for library research, documentation, and document analysis. The results of the study show 1) the form of interaction carried out by Hindus in the Buleleng Traditional Village uses a form of associative interaction, namely interaction that leads to the unification between individuals, individual groups and between groups. 2) the implementation of Tri Parārtha's teachings, namely in the form of selfless devotion is the concept of compassion, then realizing it in the form of sharing in the form of property (material) as well as providing labor sincerely is the concept of having (punia) teachings, the implementation of the teachings of bhakti is an attitude of respect by respecting elders, devotion to Ida Sang Hyang Widhi Wasa by worshiping or praying. 3) the implications of the implementation of the Tri Parārtha teachings in the life of Hindus in the Buleleng Traditional Village, namely the spontaneous increase in the attitude of compassion, affection and devotion possessed by Hindus to create harmony, then the nature of giving or giving without strings attached materially or in the contribution of energy appears. , the form of devotion is carried out not only devotion to God but the manifestation of devotion to others will also always create a harmonious life